2017
DOI: 10.1515/rjr-2017-0006
|View full text |Cite
|
Sign up to set email alerts
|

Permeabilization surgery of the upper respiratory tract and its effects on sleep fragmentation and REM sleep

Abstract: Usually, patients with sleep disorders may complain of tiredness, fatigue, daytime sleepiness, difficulty in concentrating, and can reach up to falling asleep in inappropriate situations – condition known as the Pickwick syndrome. To avoid these unpleasant symptoms, a series of surgical procedures regarding the anatomical structures involved in sleep apnea were developed.The article is a general review regarding the sleep disorders and the influence of upper airways permeability on the quality of sleep and the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…In a study published in 2017, we demonstrated the effect of the permeabilization surgery of the upper respiratory tract upon sleep fragmentation and REM sleep. The PSG performed 6 months after the surgical interventions revealed a decrease in the arousal index and a better REM sleep score (decrease of Stage 1 and Stage 2) 40 .…”
Section: Discussionmentioning
confidence: 88%
“…In a study published in 2017, we demonstrated the effect of the permeabilization surgery of the upper respiratory tract upon sleep fragmentation and REM sleep. The PSG performed 6 months after the surgical interventions revealed a decrease in the arousal index and a better REM sleep score (decrease of Stage 1 and Stage 2) 40 .…”
Section: Discussionmentioning
confidence: 88%